Defining the language assessment literacy gap: Evidence from a parliamentary inquiry. (July 2013) - Pill, John; Harding, Luke
This study identifies a unique context for exploring lay understandings of language testing and, by extension, for characterizing the nature of language assessment literacy among non-practitioners, stemming from data in an inquiry into the registration processes and support for overseas trained doctors by the Australian House of Representatives Standing Committee on Health and Ageing. The data come from Hansard transcripts of public hearings of the inquiry. Sections of the data related to language and language testing (as part of the current registration process for doctors seeking employment in Australia) were identified and coded using a thematic analysis. Findings reveal misconceptions about who is responsible for tests and for decisions based on scores in this context, as well as misconceptions about language testing procedures. Issues also emerge concerning the location of expertise in language and language testing. Discussion of these findings contributes to current debate within the language testing community (e.g., Taylor, 2009) about where responsibility lies for increasing language assessment literacy among non-practitioner stakeholders and how this might best be achieved.